COVID-19 in LAC : High Frequency Phone Surveys - Results First Wave - Ballon, Paola (World Bank, Washington, DC, 2021)
Unemployment is rising quickly and affected households are losing their main source of incomes. There is an obvious need for speeding up public intervention in the areas of virtual learning and access to medical attention and medicines across most vulnerable households. Reducing food consumption is the main mechanism to cope with the crisis for most households across the region. Despite a large rate of approval for governments’ interventions, lack of financial support to population, lack of enforcement or late response are the key area of public dissatisfaction. Unsurprisingly, there is a wide variation in abidance with lock-down measures mandated across countries. In countries like Bolivia, El Salvador, Honduras, and Peru over 90 percent of the population report to respect and follow the lockdown.